Abnormal Alpha Rhythm During Self-Referential Processing in Schizophrenia Patients - Jia, Shikui; Liu, Miaomiao; Huang, Peiwen; Zhao, Yanli; Tan, Shuping; Go, Ritsu; Yan, Tianyi; Wu, Jinglong (Frontiers in Psychiatry, 2019)
Schizophrenia patients exhibited an abnormal representation of cognitive psychology when they recognized objects related to themselves. This cognitive process is associated with self-referential processing. In this study, the self-referential memory (SRM) task was performed by 18 schizophrenia patients and 18 healthy controls. In the encoding stage of the SRM task, the behavioral experiment data and electroencephalogram (EEG) data were recorded in three experimental conditions (self-referential condition, other-referential condition, and physical condition). For data analysis, the electrophysiological performance of the time-frequency distribution, phase lag index (PLI) strengths, phase synchronization connectivity and brain-network properties were assessed in schizophrenia patients compared to healthy controls. We found that schizophrenia patients exhibited abnormal alpha oscillation characteristics at the time of 100-300 ms post-stimulus during the self-referential condition, which consisted of diminished time-frequency distributions over the prefrontal, parietal, and occipital regions, lower functional connectivity strengths of the PLI in the parietal and occipital areas, the higher global efficiency and the lower characteristic path length, and the nodal efficiency of local areas (increased nodal efficiency in temporal regions and decreased nodal efficiency in occipital region) for dynamic network topology properties. Furthermore, the evoked power of alpha band during the self-referential condition was significantly correlated with the SRM bias score in the patients (r=0.595, p=0.009). These results provided electrophysiological evidence and supported the hypothesis that an abnormal alpha rhythm might be the principal factor of dysfunctional self-referential processing in schizophrenia patients.